Relationship between body composition, anthropometry and physical fitness in under-12 soccer players of different positions - Aurelio, J.; Dias, E.; Soares, T.; Jorge, G.; da Cunha Espada, M. A.; Filho, D. M. P.; Pereira, A.; Figueiredo, T. (International Journal of Sports Science, 2016)
This study aimed to investigate the relationship between body composition, anthropometry and physical fitness in under-12 soccer players who play in different positions. Eighteen players underwent a battery of tests, in body composition and anthropometry significant differences were observed in weight (44.0 ± 4.6 vs. 35.6 ± 4.0 kg; p = 0.04) and body mass index (18.1 ± 1.0 vs. 16.1 ± 1.2 kg/cm2; p = 0.01) between defensive and midfield players. In physical fitness differences occurred between the results in handgrip strength between defenders and forwards (21.3 ± 2.8 vs. 25.4 ± 3.7 kg; p = 0.04) and midfielders and forwards (20.5 ± 2.0 vs. 25.4 ± 3.7 kg; p = 0.04)